Successful conversion surgery of distal pancreatectomy with celiac axis resection (DP-CAR) with double arterial reconstruction using saphenous vein grafting for locally advanced pancreatic cancer: a case report - Yoshiki Murase; Daisuke Ban; Aya Maekawa; Shuichi Watanabe; Yoshiya Ishikawa; Keiichi Akahoshi; Kosuke Ogawa; Hiroaki Ono; Atsushi Kudo; Toshifumi Kudo; Shinji Tanaka; Minoru Tanabe (Surgical Case Reports)
Abstract Background Pancreatic cancer is a disease with a poor prognosis, requiring multidisciplinary treatment combining chemotherapy and surgery for effective management. Distal pancreatectomy with celiac axis resection (DP-CAR) is a surgical intervention performed for locally advanced pancreatic cancer, but the benefit of arterial reconstruction in DP-CAR is unclear. Case presentation A 49-year-old man with pancreatic cancer was referred to our hospital. Imaging revealed a 54-mm tumor mainly in the pancreatic body, but with arterial infiltration including into the celiac, common hepatic, left gastric, splenic and gastroduodenal arteries. Distant metastases were not detected. The patient was diagnosed with unresectable locally advanced pancreatic cancer and chemoradiotherapy was planned. Three cycles of gemcitabine (1000 mg/m2) plus nab-paclitaxel (125 mg/m2) every 4 weeks were followed by irradiation (2 Gy/day, total 50 Gy over 25 days) together with S-1 administration (80 mg/m2/day). A partial response (PR) according to Response Evaluation Criteria in Solid Tumors (RECIST) was achieved, so surgical intervention was considered. Because the tumor had invaded the root of the gastroduodenal artery, we performed DP-CAR with resection of the gastroduodenal artery, followed by arterial reconstruction of the proper hepatic and left gastric arteries, anastomosed with the abdominal aorta using a great saphenous vein graft in the shape of a “Y”. Histopathology showed that 60% of tumor cells were destroyed by the chemoradiotherapy, defined as grade IIb in the Evans classification. No malignancy was detected at the surgical margin, including the celiac artery, gastroduodenal artery or pancreatic stump; thus R0 surgery was successful. S-1 (80 mg/day) was administered as adjuvant chemotherapy for 6 months. The patient is now doing well without recurrence for > 2 years after the initial treatment (more than 16 months after surgery). Conclusion For locally advanced pancreatic cancer, multidisciplinary treatment combining gemcitabine/nab-paclitaxel-based chemoradiotherapy and then DP-CAR surgery with gastroduodenal artery resection and arterial reconstruction using saphenous vein grafting enabled R0 resection in this patient and led to a favorable long-term prognosis.